Wavelength tunable properties of highly oriented colloidal acrylate latex film / Helyati Abu Hassan Shaari, Mohammad Syuhaimi Ab. Rahman and Rahmah Mohemed - Abu Hassan Shaari, Helyati; Ab. Rahman, Mohammad Syuhaimi; Mohemed, Rahmah (Universiti Teknologi MARA, Perlis, 2018)
Colloidal acrylate latex film with wavelength tunable properties was simply fabricated by depositing colloidal monodisperse acrylate spheres with pre-vulcanized latex (PVL). The resultant film exhibited a reversible reflectance wavelength when highly oriented into high elongation upon interaction with incident light. Benefiting from the elastic characteristic of natural rubber latex, the film produced can withstand elongation up to 600% elongation to give various reflectance wavelengths at different strain levels. The reversible wavelength response of the colloidal acrylate latex film suggests its potential to be used as a main material for in situ monitoring of stress and strain devices